2019
DOI: 10.29309/tpmj/2019.26.04.3355
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Site Infection;

Abstract: Objectives: Efficacy of postoperative Povidone-Iodine pro­phylaxis and surgical site infection in appendectomy surgery. Study Design: Randomized clinical trial. Place and Duration: Department of Surgery, Liaquat University Hospital Jamshoro/Hyderabad from March 2016 to November 2017. Subjects and Methods: Diagnosed cases of acute appendicitis with classical clinical presentation were included in the study protocol. 60 patients were those, who were applied 1% povidone-iodine solution (cases) to wound post opera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…It is reported that blood transfusion is the most common and easy route of transmission of many infectious diseases like HBV, HCV, HIV, syphilis, malaria and so on. To ensure the safe blood transfusion different serological tests are performed before the transmission of blood 11 .…”
Section: Discussionmentioning
confidence: 99%
“…It is reported that blood transfusion is the most common and easy route of transmission of many infectious diseases like HBV, HCV, HIV, syphilis, malaria and so on. To ensure the safe blood transfusion different serological tests are performed before the transmission of blood 11 .…”
Section: Discussionmentioning
confidence: 99%